Refuge denied : the St. Louis passengers and the Holocaust - Ogilvie, Sarah A. (The University of Wisconsin Press, 2006)
The ordeal of the refugee ship St. Louis has become a symbol of the worlds indifference to the plight of European Jewry on the eve of the Holocaust. In the spring of 1939, more than nine hundred Jewish refugees boarded theSt. Louis in Hamburg, Germany, hoping to escape escalating oppression by the Nazi government. The ship was denied entry, and nearly all of its passengers denied asylum, by Cuba and the United States. Returning on an uncertain voyage to Europe, the refugees eventually were accepted by four western European countries, but only the 288 sent to England evaded the Nazi grip that closed upon continental Europe a year later. Although the episode of the St. Louis is well known, the actual fates of the passengers, once they disembarked, slipped into historical obscurity. Prompted by a former passengers curiosity, Sarah Ogilvie and Scott Miller of the United States Holocaust Memorial Museum set out to discover what happened to each of the 937 passengers. Their investigation, spanning ten years and half the globe, took them to unexpected places and produced surprising results.